2004
DOI: 10.1103/physrevb.69.014104
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between the magnetism and dielectric properties inEu1xBax

Abstract: The dielectric constant of the quantum paraelectric EuTiO 3 exhibits a sharp decrease at about 5.5 K, at which temperature antiferromagnetic ordering of the Eu spins simultaneously appears, indicating coupling between the magnetism and dielectric properties. A similar feature has also been detected in Eu 1Ϫx Ba x TiO 3 (0Ͻxр0.2). The random-bond model within the framework of the transverse-field Ising model and the site dilution model based on the Heisenberg model are successfully applied to the Eu 1Ϫx Ba x Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…16,17 Likewise "chemical strain," i.e., doping at the A site with larger divalent ions, has been shown to induce ferroelectricity, e.g., in alloys with BaTiO 3 . 18 The latter is particularly intriguing, as multiferroic (Eu,Ba)TiO 3 ceramics fulfill the requirements for a solid state search for the electric dipole moment of electron. 19 In this work, we revisit bulk EuTiO 3 , with a particular focus on the possibility that the ground state is not, in fact, the high-symmetry P m3m perovskite prototype, but a lower symmetry structure possessing rotations or tilts of the oxygen octahedra.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Likewise "chemical strain," i.e., doping at the A site with larger divalent ions, has been shown to induce ferroelectricity, e.g., in alloys with BaTiO 3 . 18 The latter is particularly intriguing, as multiferroic (Eu,Ba)TiO 3 ceramics fulfill the requirements for a solid state search for the electric dipole moment of electron. 19 In this work, we revisit bulk EuTiO 3 , with a particular focus on the possibility that the ground state is not, in fact, the high-symmetry P m3m perovskite prototype, but a lower symmetry structure possessing rotations or tilts of the oxygen octahedra.…”
Section: Introductionmentioning
confidence: 99%
“…In recent experiments, K. Z. Rushchanskii et al 15 found ferroelectric hysteresis loop around 130 K and antiferromagnetism below T N = 1.9 K in the same composition. While H. Wu et al 16 investigated theortically the intrinsic coupling between magnetism and dielectric properties in Eu 1-x Ba x TiO 3 (0 ≤ x ≤ 0.2), T. Wei et al 17 reported dielectric constant and electrical polarization in polycrystalline samples (0 ≤ x ≤ 1). It was found that while x ≤ 0.15 is paraelectric, ferroelectricity develops in x > 0.2 as evidenced by ferroelectric hysteresis loop.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetoelectric interaction is described by Eq. (4), which has been first established to investigate the impurity effect [4]. As has been pointed out in the previous section, two kinds of coupling form have been proposed: one is based on the soft-mode theory [12] and the other is based on TIM [4].…”
Section: Models and Analysismentioning
confidence: 99%
“…Here, the external fields include the electric field E and the magnetic field h, and the dielectric properties include the polarization p and the dielectric capacitance ε . We think our work provides a thorough research into the magnetodielectric properties of EuTiO 3 , and it also helps us to better understand the doped system [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation